A consideration of organisational sustainability in the SME context: A resource-based view and composite model. Issue 5 (27th May 2014) - Darcy, Colette; Hill, Jimmy; McCabe, TJ; McGovern, Philip
Abstract : Purpose: – The purpose of this paper is to consider organisational sustainability in the small- to medium-sized enterprises (SME) context focussing on a resource-based view. The paper overlays two contrasting perspectives: those of the SME and human resource (HR) perspectives to allow for the development of a composite model of organisational sustainability for SMEs. Design/methodology/approach: – The paper overlays four models of Carson's (1985, 1990) small firm evolution and unique characteristics of SMEs; Wright et al. 's (2001) pertaining to the application of the resource-based view of the firm perspective to strategic HR and Boudreau and Ramstad (2005) model of effectiveness, efficiency and impact of talentship. The paper, in particular, considers the human resource management (HRM) perspectives pertaining to the overlay and considers how these might impact organisational sustainability. Findings: – An outcome of the paper is the development of a composite model to the SME and HR perspectives of organisational sustainability and its applicability to the SME context. Research limitations/implications: – The paper suggests a number of emergent areas for future research. Future research should focus on the intangible aspects and softer elements of the organisational resource base. The majority of work in this area is grounded in the positivist paradigm. Future research should consider a pluralists perspective and draw on traditions of the post-positivist paradigm, for example, social constructionism. Practical implications: – SME-support agencies and consultants who work with SMEs need, therefore, to work with them in assessing their competency spectra and then to help them develop the talent pools required to effect continued growth and success. In doing so SMEs need to be guided towards a better understanding of the traditional temporal cycle of recruitment; in essence, they need to ensure that they have the right competency set in situ in the early stages of the firms' development. Originality/value: – This paper is unique in its approach to the examination of sustainability within the context of SMEs and, in particular, the HRM aspects which contribute towards organisational survival, growth and sustainability.